Legal deposit in the Sultanate of Oman: The Law of Press and Publications and its role in building Oman’s culture of democracy - Saleem, Naifa Eid; Al Kindi, Abdullah Khamis; Al-Rahbi, Khalifah (International Journal of Knowledge Content Development & Technology, 2017)
Omani citizens participate in the making of a culture of democracy through the implementation of the legal deposit or the Law of Press and Publications. Legal deposit is the law that requires the meant intended, whether they are publishers, printers or authors, to submit certain copies of their work or publications to a repository, usually a library. The present study aims to explore the reality of the Omani Law of Press and Publications and to discover how the law defines the term "publications". In addition to the role of this law in building the Omani culture of democracy, the study uses an interpretive research paradigm of applied unstructured interviews and content analysis. Four printers were interviewed. With regard to the findings, the study determined that definition of the term "publications", according to the law, is very general and covers different items, and the Law of Press and Publications plays an essential role in the building of Oman’s culture of democracy. The study also found that four of the printers participated in creating the Omani culture by depositing the requested copies of his publications, although one of them is not happy to be asked to do this. URL: http://ijkcdt.net/xml/09911/09911.pdf